Child Protection Policy and Behavioral Management Practices at a Public Elementary School in Rizal, Philippines - Castino, Liberty Gomintong (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study determined the child protection policy and behavioural management practices of a public elementary school in Rizal, Philippines in the year 2018-2019. It employed the quantitative descriptive correlational method of research which used questionnaires as the means to gather data. Results revealed that the practices observed by the respondents in child protection in terms of anti- bullying and discrimination are educating students on how to deal with bullying properly and strictly implementing the anti-bullying campaign. The behavioural management practices observed by the respondents in terms of anti-bullying and discrimination are making it more concrete for everyone the difference between play and fight and delivering praise and rewards to increase appropriate behavior. The practices observed by the respondents in child protection in terms of abuse are giving opportunities to pupils to speak and express their views and opinions especially when it comes to social interactions, gaining the trust of students through one-on-one coaching. The practices observed in child protection in terms of violence and exploitation are educating students about their rights as children and informing pupils that there are different agencies that handle issues on violations against the rights of the youth, and giving special attention to the misbehaved pupils. Lastly, there is a significant difference between the respondents in implementation of child protection policy and their behavioural management practices and that there is a positive correlation between the behavioural management practices of the respondents when grouped according to their profile.